The Utility of Recanalized Umbilical Vein Graft to the Hepato-pancreato-biliary Surgeon. (April 2013) - Rochon, Caroline; Sheiner, Patricia A.; Sharma, Joyti; Rodriguez-Davalos, Manuel I.; Savino, John; Facciuto, Marcelo E.
Background. The authors recently published their experience of recanalizing umbilical veins in deceased liver donors, with recanalized umbilical veins as vascular conduits for meso-Rex bypass procedures. They have since found recanalized umbilical veins to be an excellent, easy to harvest vascular conduit that can be used for multiple vascular procedures and repair. Here, they report their experience using this vessel for bypass and vascular reconstruction.Methods. They have recanalized umbilical veins and used them in a total of 5 Meso-Rex bypasses; 5 pancreaticoduodenectomies; 1 left hepatic trisegmentectomy with right portal vein (PV) resection and reconstruction; 1 right hepatectomy and 1 adrenalectomy, both with partial inferior vena cava (IVC) resection and reconstruction; 1 coronary-Rex bypass shunt for extrahepatic PV thrombosis; and 1 orthotopic liver transplantation with infrahepatic IVC anastomotic dehiscence patched with umbilical vein graft. Umbilical veins were dilated mechanically and used in situ for the meso-Rex bypass surgery; they were ligated in the space of Rex and then dilated ex vivo otherwise to be used as interposition grafts or a vein patch.Results. A total of 15 hepato-pancreato-biliary procedures were done using the recanalized umbilical vein as graft; 2 patients required thrombectomy postoperatively with reexploration, venotomy, thrombectomy with fogarty catheter, and venotomy closure.Conclusion. The umbilical vein graft is a fine vascular conduit and can serve many purposes in hepatobiliary surgery.